Integrated total pelvic floor ultrasound in pelvic floor dysfunction - A.J. Hainsworth; T. Gala; L. Johnston; D. Solanki; L. Ferrari; A.M.P. Schizas; G. Santoro (Continence, 2023)
Integrated total pelvic floor ultrasound is a combination of endoanal, transperineal, and endovaginal ultrasound used for the static and dynamic assessment of the entire pelvic floor. It can be used as a screening investigation for defaecatory dysfunction so that defaecatory radiological imaging may be avoided. It enables assessment of concomitant pelvic floor disorders such as anterior and middle compartment dysfunctions. Other advantages include the ability to perform in the outpatient rooms in a one stop clinic, alongside clinical assessment, and anorectal physiology, whilst avoiding separate radiology appointments and radiation exposure. Moreover, it has the potential to be used as a visual biofeedback tool.Integrated total pelvic floor ultrasound is user dependent and currently there are no fixed protocols for performance or reporting protocols. As integrated total pelvic floor ultrasound becomes more commonplace this is something which should be addressed.This article outlines the clinical utility, practicalities, and guidance for the interpretation of imaging which may be used. It is the basis for integrated total pelvic floor ultrasound workshops which have been held at the International Continence Society conference over the last 5 years.